The Active Society Revisited: A Framework for the Study of Social Innovation - Kesselring, Alexander (Teorie vědy / Theory of Science, 2010)
The aim of this paper is to show how the theory of an active society by Amitai Etzioni can provide a theoretical framework for the study of innovation processes – in particular social innovation, which is generally defined here as the implementation of a new social practice aimed at solving social problems and/or meeting social needs. An active society is a society in which collectivities (social groups) have the potential to articulate values and needs, to participate in consensus building processes and decision processes, to develop organisational structures and to realise values through collective social action. This paper discusses the general differentiation and interrelation between culture, structure and agency which is the fundament of the theory of an active society and additionally presents a systematisation which combines these domains with the “elements” (consciousness, commitment, knowledge, power) and “processes” (consensus building, mobilisation, decision making, control/guidance) that Etzioni perceives as the main dimensions of the active orientation. This systematisation can be seen as an adaptation of Etzioni’s theory which tries to make the interrelation between different theoretical dimensions more explicit.